The ambiguities of surveillance as care and control: Struggles in the domestication of location-tracking applications by Danish parents - Widmer Sarah; Albrechtslund Anders (Nordicom Review)
The implicit ambiguity of surveillance as both care and control has been a key theoretical issue in social science research on surveillance practices and technologies. This article addresses this ambiguity empirically by examining how parents using – or not using – location-tracking apps to monitor their children negotiate this tension. Drawing on 17 semistructured interviews conducted with parents in different regions of Denmark, we examine the struggles of these parents to fit this technology into their world and to reconcile their uses with ideals of trust, privacy, and good parenting. By highlighting how users and non-users perceive and negotiate the controlling affordances of tracking apps, we emphasise the potential for negotiation, contestation, and resistance raised by this technology, and the contingent nature of its appropriation and effects. Thereby, it brings nuances to techno-pessimistic accounts of child tracking and calls for further empirical studies examining how these technologies are experienced in practice.